Treatment of catecholaminergic polymorphic ventricular tachycardia in mice using novel RyR2-modifying drugs. (15th January 2017) - Li, Na; Wang, Qiongling; Sibrian-Vazquez, Martha; Klipp, Robert C.; Reynolds, Julia O.; Word, Tarah A.; Scott, Larry; Salama, Guy; Strongin, Robert M.; Abramson, Jonathan J.; Wehrens, Xander H.T.
Abstract: Rationale: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a potentially lethal arrhythmic disorder caused by mutations in the type-2 ryanodine receptor (RyR2). Mutant RyR2 cause abnormal Ca 2 + leak from the sarcoplasmic reticulum (SR), which is associated with the development of arrhythmias. Objective: To determine whether derivatives of tetracaine, a local anesthetic drug with known RyR2 inhibiting action, could prevent CPVT induction by suppression of RyR2-mediated SR Ca 2 + leak. Methods and results: Confocal microscopy was used to assess the effects of tetracaine and 9 derivatives (EL1–EL9) on spontaneous Ca 2 + sparks in ventricular myocytes isolated from RyR2-R176Q/+ mice with CPVT. Whereas each derivative suppressed the Ca 2 + spark frequency, derivative EL9 was most effective at the screening dose of 500 nmol/L. At this high dose, the Ca 2 + transient amplitude was not affected in myocytes from WT or R176Q/+ mice. The IC50 of EL9 was determined to be 13 nmol/L, which is about 400 × time lower than known RyR2 stabilizer K201. EL9 prevented the induction of ventricular tachycardia observed in placebo-treated R176Q/+ mice, without affecting heart rate or cardiac contractility. Conclusions: Tetracaine derivatives represent a novel class of RyR2 stabilizing drugs that could be used for the treatment of the potentially fatal disorder catecholaminergic polymorphic ventricular tachycardia.